Analysis of vaginal delivery outcomes among pregnant women in Wuhan, China during the COVID‐19 pandemic. Issue 1 (19th May 2020) - Liao, Jing; He, Xiaoyan; Gong, Qing; Yang, Lingyun; Zhou, Chunhua; Li, Jiafu
Abstract: Objective: To study vaginal delivery outcomes and neonatal prognosis and summarize the management of vaginal delivery during the COVID‐19 pandemic. Methods: A retrospective analysis of medical records and comparison of vaginal delivery outcomes between 10 pregnant women with clinical diagnosis of COVID‐19 and 53 pregnant women without COVID‐19 admitted to Zhongnan Hospital of Wuhan University between January 20 and March 2, 2020. Results of laboratory tests, imaging tests, and SARS‐CoV‐2 nucleic acid tests were also analyzed in neonates delivered by pregnant women with clinical diagnosis of COVID‐19. Results: There were no significant differences in gestational age, postpartum hemorrhage, and perineal resection rates between the two groups. There were no significant differences in birth weight of neonates and neonatal asphyxia rates between the two groups. Neonates delivered by pregnant women with clinical diagnosis of COVID‐19 tested negative for SARS‐CoV‐2 infection. Conclusions: Under the premise of full evaluation of vaginal delivery conditions and strict protection measures, pregnant women with ordinary type COVID‐19 can try vaginal delivery without exacerbation of COVID‐19 and without increasing the risk of SARS‐CoV‐2 infection in neonates. Abstract : Pregnant women with ordinary type COVID‐19 could try vaginal delivery without increasing the risk of SARS‐CoV‐2 infection in their neonates.